Scientific Literacy Skills Based on Local Wisdom and Pancasila Student Profile: Supporting Quality Education (SDG 4) - Mustika Wati; Nur Afifah Azzahra; Qamariah Qamariah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2027)
Objective: Scientific literacy is an essential competency for students in responding to rapid developments in science and technology. However, students’ scientific literacy skills in Indonesia remain below international standards, indicating the need for contextual learning approaches. This study aims to analyze the scientific literacy profile of senior high school students based on local wisdom and the Pancasila Student Profile. This study contributes to achieving Sustainable Development Goal (SDG) 4 by supporting quality education through contextual and meaningful science learning. Method: A descriptive quantitative approach using a survey method. The participants consisted of 202 senior high school students from Balangan and Tabalong Regencies, South Kalimantan, Indonesia. Data were collected using a scientific literacy instrument consisting of 16 multiple-choice questions integrated with local wisdom and Pancasila Student Profile values. The collected data were analyzed using the Rasch Model with the assistance of the Winstep application to determine students’ ability levels, item difficulty, and instrument reliability. Results: The results showed that students’ scientific literacy skills were categorized as very high (8.91%), high (23.27%), sufficient (31.68%), low (28.71%), and very low (7.43%). The instrument demonstrated adequate reliability with a person reliability value of 0.69 and Cronbach’s alpha value of 0.75. These findings indicate that most students have moderate scientific literacy abilities, but further improvement is required. Novelty: To provide a novel contribution by assessing physics scientific literacy using instruments integrated with local wisdom and the Pancasila Student Profile, providing a contextual approach to supporting quality science education aligned with SDG 4.